EFFECT OF TIERED REFERRALS IMPLEMENTATION ON LEVEL OF MATERNAL RISK - Suryani Yuliyanti; Radite Sekar Hapsari; Ratnawati (Universitas Airlangga, 2026)
Background: Effective and efficient medical referrals, particularly in terms of accurate diagnosis, play a crucial role in reducing the risk of maternal mortality. However, certain healthcare services have not implemented adequate referral practices. Aims: This study aims to analyze the effect of tiered referral system policies on the risk of pregnancy and labor among inpatient mothers admitted to the emergency unit of Islamic Sultan Agung Hospital Semarang. Methods: This cross-sectional study assessed the medical records of 819 women who were admitted to the hospital through the emergency unit and had a history of antenatal care visits at the obstetric clinic at Islamic Sultan Agung Hospital Semarang. The research instrument was the Poedji Rochjati Scorecard and medical record data. Data were analyzed using the Mann-Whitney test. Results: 479 (58,5%) patients came before the tiered referral policies, and those who came after were 340 (41.5%). The Poedji Rochjati average score before the tiered referral policy (7.6) and after the tiered referral policy (6.5). Mann-Whitney analysis showed differences in maternal risk scores before and after implementing tiered referrals (p=0.001). Conclusion: It is necessary to review the tiered referral and hospital-type policy. Hence, the tiered referrals policy can be applied to support effective and efficient referral services. Keywords: tiered referrals, Poedji Rochjati score, labor mother